Zinc Transporter ZmLAZ1-4 Modulates Zinc Homeostasis on Plasma and Vacuolar Membrane in Maize - Liu, Bingliang; Yu, Haoqiang; Yang, Qinyu; Ding, Lei; Sun, Fuai; Qu, Jingtao; Feng, Wenqi; Yang, Qingqing; Li, Wanchen; Fu, Fengling (Frontiers in Plant Science, 2022)
Zinc is an essential micronutrient for plant growth and development, and functions as a cofactor for hundreds of transcription factors and enzymes in numerous biological processes. Zinc deficiency is common abiotic stress resulting in yield loss and quality deterioration of crops, but Zinc excess causes toxicity for biological systems. In plants, Zinc homeostasis is tightly modulated by Zinc transporters and binding compounds that uptake/release, transport, localize and store Zinc, as well as their upstream regulators. Lazarus 1 (LAZ1), a member of DUF300 protein family, functions as transmembrane organic solute transporter in vertebrates. However, the function of LAZ1 in plants is still obscure. In the present study, the ZmLAZ1-4 protein was confirmed to bind to Zinc ion by bioinformatic prediction and thermal shift assay. Heterologous expression of ZmLAZ1-4 in the Zinc-sensitive yeast mutant, Arabidopsis and maize significantly facilitated accumulation of Zn2+ in transgenic lines, respectively. The result of subcellular localization exhibited that ZmLAZ1-4 was localized on the plasma and vacuolar membrane, as well as chloroplast. Moreover, the ZmLAZ1-4 gene was negatively co-expressed with ZmBES1/BZR1-11 gene through co-expression and RT-qPCR analysis. The results of yeast one-hybrid and dual-luciferase assay suggested that ZmBES1/BZR1-11 could bind to ZmLAZ1-4 promoter to inhibit its transcription. All results indicated that ZmLAZ1-4 was a novel Zinc transporter on plasma and vacuolar membrane, and transported Zinc under negative regulation of the ZmBES1/BZR1-11 transcription factor. The study provides insights into further underlying the mechanism of ZmLAZ1-4 regulating Zinc homeostasis.